A contingency theory approach for construction companies in Malaysia during the period of economic crisis: survival strategies - Bakar, Abu Hassan Abu; Said, Ilias; Abdul Razak, Arman; Yusof, Mohamad Nizam; Awang, Aidah (2008)

(untitled)
The ability of the construction industry to respond to changes in its environment has always been the subject of debate. There are some organizations that are very successful in responding to changing its outlook and fundamentals but when viewed as a whole the construction industry shows slow response to changes in its environment. Contingency theory is a concept that promotes flexibility in choice of actions to success or survives in an uncertain environment. This theory defines that there is no best way of doing this and that a strategy that is effective in some situations may not be effective and successful in others. This is concept papers which try to establish critical survival practices by local construction companies. The objective of this paper is to determine survival strategies by evaluate the success factor practices by local companies. Reviews of Lansley’s and others works will be used to generate factors/variables for further testing. The expected result will come up with the pattern of behavior of local construction companies over a period of time particularly during the two economic down turning 1986 and 1997.